2021
DOI: 10.1002/jobm.202100334
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor GlbHLH regulates hyphal growth, stress resistance, and polysaccharide biosynthesis in Ganoderma lucidum

Abstract: Basic helix-loop-helix (bHLH) transcription factors (TFs) participate in many physiological and cellular processes in eukaryotes. However, their functions remain unclear in the macro basidiomycete Ganoderma lucidum (G. lucidum).In this study, a gene encoding bHLH TF, GlbHLH, was identified in G. lucidum. The knockdown of GlbHLH by RNA interference reduced hyphal growth, hyphal branching, and resistant to osmotic, oxidative, and cell wall stress. The content of cell wall components β-1,3 glucan and chitin and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Further analyses revealed that 27 DEGs were enriched in the term ‘growth’ in GO_level 2 and 25 out of these genes were significantly downregulated (Figure 6a and Table S4 ). Hyphal branching is an important indicator of the mycelial growth process of filamentous fungi (Wu et al., 2016 ; Yang, Zhang, He, et al., 2022 ). Many protein kinases and septins are involved in the regulation of lateral branch formation (Harris, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Further analyses revealed that 27 DEGs were enriched in the term ‘growth’ in GO_level 2 and 25 out of these genes were significantly downregulated (Figure 6a and Table S4 ). Hyphal branching is an important indicator of the mycelial growth process of filamentous fungi (Wu et al., 2016 ; Yang, Zhang, He, et al., 2022 ). Many protein kinases and septins are involved in the regulation of lateral branch formation (Harris, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Polysaccharides are the major feature of B. striata . Transcription factors regulate BSP biosynthesis generally through interaction with structural genes (He et al., 2018; He et al., 2019; Yang, Zhang, et al., 2021). To further understand the key factors involved in BSP synthesis, we carried out an integrative analysis governing the BSP biosynthesis pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Glycogen branches can increase the water solubility of glycogen to facilitate glycogen storage and raise the number of non-reducing ends, thereby allowing biological organisms to aggregate when they need glycogen for energy. GBE regulates glycogen metabolism and participates in the response to abiotic stress ( Yang et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%